Synthesis, thermal and performance properties of poly(urethane-dimethylsiloxane) anionomers. Part II. Thermal and performance properties - Byczyński, Ł.; Król, P. (Polimery, 2013)
Poly(urethane-dimethylsiloxane) anionomers (PUR-PDMS) were synthesized in two- and three-stage process, with the use of isophorone diisocyanate (IPDI) and poly(oxytetramethylene) diol (PTMG), partially replaced by polydimethylsiloxane diols (PDMS) with different chain structures. 2,2-bis(hydroxymethyl)propionic acid (DMPA) neutralized with triethylamine (TEA) was used as the ionogenic component built into the polyurethane chain and ethylenediamine (EDA) as the extender. Studies on the thermal degradation using TGA analysis in nitrogen or air atmosphere enabled us to investigate the decomposition process and to evaluate the effect of the presence of polysiloxanes on the thermal stability of PUR-PDMS anionomers. The degradation in nitrogen took place in two stages, while in air the decomposition mechanism was more complicated and involved four stages. It was observed that the temperature corresponding to the maximum rate of the second decomposition stage decreases with an increase in the content of PDMS built-into the polymer chain, which indicates a small increase in the thermal stability of polysiloxane-modified PUR anionomers. From the preliminary performance tests it appears that the hydrophobic fragments of the built-in polysiloxane have a tendency to migrate towards the polymer surface in the produced PUR-PDMS coatings, with the advantage of the increased hydrophobicity but at the expense of a decreased abrasion resistance of the coatings.